Effectiveness of Soya Beans Versus Diaphragmatic Breathing Exercise on Level of Menopausal Symptoms among Postmenopausal Women (International Journal of Nursing Education, 2020)
The study was conducted to evaluate the effectiveness of soya beans versus diaphragmatic breathingexercise on level of menopausal symptoms among postmenopausal women. Quasi experimental design wasadopted for the study. The structured interview questionnaire was developed to collect the data. The samplewere selected by simple random sampling (lottery) method and data collection was carried out among 70postmenopausal women in selected villages. Pretest was conducted with Modified Greene Climacteric Scaleand Post test was conducted on 21st day. The findings revealed that the mean score level of menopausalsymptoms among postmenopausal women in study group I was 39.25 in pre test and 36.34 in post testrespectively. The paired ‘t’ value of 1.69 which is significant at p<0.05 .It shows that soya beans was effectivein reducing the menopausal symptoms. In study group II the mean score on level of menopausal symptomsamong postmenopausal women was 36.71 in pre test and 29.62 in post test respectively . The estimatedpaired ‘t’ value was 1.69 which was also significant at p<0.05. In this study the investigator concludedthat soya beans and diaphragmatic breathing exercise are effective in reducing menopausal symptoms, butdiaphragmatic breathing exercise was more effective than soya beans.